Approaches to Integration of Knowledge: A Study of Al-Ghazali And Alwani’s Views - Sayyid Muhammad Yunus Gilani; Tazul Islam (International Islamic University Malaysia, 2024)
Volume:15 No: 2 (page:389–410)